“TERPI” AS A QUANTITY OF THERMODYNAMIC POTENTIAL ENERGY SUPPLEMENTARY TO THE CONCEPT OF WORK AND HEAT - RHA Sahirul Alim (Indonesian Journal of Chemistry, 2003)
Isothermal reversible thermodynamic processes were studied, where there will not occur flow of heat (q) in the system in accord with the second law of thermodynamic. It appear that the energy flow in the system cannot be explained adequately by considering the flow of P,V - work, usually indicated by w, in accordance with the first law, that is,  ΔU = q + w with q = 0.  Therefore, it is necessary to have another kind of work energy (potential) which is not electrical to explain such as the experiment of Boyle that results in the formula PV = C for a close ideal gas system undergoing an isothermal and reversible process. In this paper, a new work potential which is called ";;terpi";; is introduced, and is abbreviated as  τ (tau) and defined as: dτ ≡  - T dSrev = - dqrev.            Therefore, dt is also not an exact differential as dw and dq. For any isothermal reversible process, it can be written:   τ = -TΔSrev, and for redox reaction, such as an electrochemical cell, it is noteworthy to distinguish between τ system (τsyst) and τ reaction (τr) which combine together to become an electrical work flow, (wel) done by the system on the surrounding, so that:ΔGr = τsyst + τr = v F E            Furthermore, the studies of phase transitions, which occur isothermally, were also considered, e.g. the evaporation of a liquid into vapour at a certain T.  The heat given to this process cannot freely flow isothermally, but first it must be  changed into terpy and then added to the enthalpy of the vapour following the equation:     τvap = -TΔSvap = -ΔHvap.